254 Visual inversion illusion in a patient with multiple sclerosis. Issue 12 (14th November 2019) - Cheema, Sanjay; Mahmud, Mohammad; Cooper, Sarah
Abstract : Background: It is possible to suddenly and temporarily experience the illusion that the world is upside down. This visual inversion illusion is rare, but has previously been reported in patients with migraine, posterior circulation stroke, traumatic brain injury, and multiple sclerosis (MS). The same illusion can be provoked in neurologically-normal aircraft pilots or astronauts under certain circumstances; and in experiments involving wearing vision-inverting goggles. Case history: We report a patient with secondary progressive MS, who for the past six months reported that 'when I get tired my eyes see everything upside-down'. These episodes occurred most evenings and resolved after a night's sleep. On examination there was evidence of previous optic neuritis and intranuclear ophthalmoplegia. MRI brain showed multiple lesions in the brainstem and visual pathways. Discussion: This case adds to the small number of reports of this phenomenon in the context of MS, and the first where it is related to fatigue. The precise anatomical substrate is unknown. It has been reported in patients with single lesions in the brainstem, vestobulocerebellum, and right parieto-occipital region. The illusion may occur due to disrupted sensory integration between visual input and other verticality signals, for example from the vestibular system.